Photography applications for cloud computing - Bamberg, Matthew (Australia : Course Technology, Cengage Learning, 2013)
The various available cloud platforms are explored and evaluated, including Dropbox, Adobe Revel, Photo Stream in iCloud, Mozy, Amazon Cloud Drive, and more. Special attention is paid to identifying how the platforms handle Raw, TIF, and JPEG photos for optimal access and security, including the maintenance of resolution throughout the uploading, editing, and saving process--
Keywords: Photography -- Computer network resources; Photography -- Digital techniques -- Computer programs; Computer file sharing -- Computer programs; Cloud computing; Image files; Web sites -- Directories